CO-CREATING EXPERIENCE IN PHYGITAL PLATFORM: EXPLORATION OF CUSTOMER EXPERIENCE AND PATRONAGE INTENTION IN RETAIL BUSINESS - Baehaqi, Muhammad; Rizana, Dani; Cahyono, Ragil Setyo; Naryananda, Habib Pijar Bawana (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
This study investigates the influence of phygital platforms on customer experience (CX) and patronage intention within the retail sector. Utilising the Stimulus-Organism-Response (SOR) framework, this research examines the impact of channel service configuration and integrated interaction as stimuli on CX and phygital platforms, which subsequently influence patronage intention. Data were obtained from 159 respondents with prior experience using phygital platforms, collected via an online questionnaire distributed through social media channels in two major provinces of Indonesia, Central Java and the Special Region of Yogyakarta. The empirical findings reveal that integrated interaction significantly enhances both CX and perceptions of phygital platforms. However, the phygital platform itself does not significantly enhance CX, it does contribute to increased patronage intention. Furthermore, CX is identified as a crucial mediating variable, exerting both direct and indirect effects on patronage intention. These results highlight the strategic importance of designing and implementing phygital platforms that effectively integrate physical and digital components to meet customer needs. JEL: D12, M15, M21.